Empreendedorismo e bricolagem sociais com participação de stakeholders em serviços de saúde - Santos, Adriana Aparecida Honório dos (2024)
With the intention of generating improvements in the lives of people and communities, social entrepreneurship seeks to solve needs not met by the market and governments, also acting in the area of health. By obtaining participation and collaboration from stakeholders, social enterprises mobilize resources to ensure that their social purpose is achieved. To this end, social managers use numerous means, such as social DIY with the participation of stakeholders, in order to meet social needs, face society's challenges and improve people's quality of life. The objective of this thesis is to explain how social entrepreneurship and social bricolage with the participation of external stakeholders occur in the health area, particularly in philanthropic and public hospitals, to provide health services to the less favored population. The structure of the thesis is composed of a systematic literature review, carried out from the collection of data in the Web of Science, Scopus and Pubmed databases (base supporting biomedicine and health sciences research) in the period from 2008 to 2023 and by an empirical investigation that uses data from 21 social entrepreneurs and hospital managers. With the systematic literature review of 56 articles, it was possible to identify the main actions of social managers in the health area, which are: the use of management practices, the search for partnerships, the use of technology and emphasis on the area of human resources. With the systematic review, it was also possible to develop a typology of the main external stakeholders and their actions. For the empirical investigation, qualitative research was carried out with multiple case studies, supported by 21 semi-structured interviews with the support of Atlas.ti24 and the analysis of documentary evidence, which deepened the knowledge of entrepreneurship and social bricolage with the participation of stakeholders in the health area. The findings demonstrated that, despite the high regulation of health, a variety of social bricolage practices are used with the participation of stakeholders. Social bricolage was used mainly in times of crisis and in challenging situations in the hospitals studied, such as lack of resources or lack of labor. As a result, a synthesis of the relationships between social bricolage with stakeholder participation for the hospital institution activities studied is proposed, which presents the three main actions of hospital managers when using social bricolage with the participation of external stakeholders, which are: the capacity of managers in fulfilling their daily management and leadership tasks, developing greater synergy with stakeholders and increasing communication channels, with the use of technology. In the end, this study shows that actions combined with social bricolage and stakeholder participation can bring benefits to hospital institutions and that social entrepreneurship actions, in the three dimensions presented, can motivate greater involvement of these partners.